SERUM PROTEIN CONCENTRATION OF SHEEP EXPERIMENTALLY POISONED BY Ipomoea asarifolia - Chaves, Daniel Praseres (2011)
In order to evaluate the serum protein concentration of sheep experimentally poisoned by Ipomoea asarifolia, four groups of five animals received diet with inclusion of 25% (G1), 50% (G2), 75% (G3) and 100% (G4) of the plant replacing to Pennisetum purpureum. Blood samples for serum protein concentration evaluation were collected at seven moments (M): before of the I. asarifolia supply (M1), and five (M2), ten (M3), 15 (M4), 20 (M5), 25 (M6) and 30 (M7) days after I. asarifolia supply. The serum concentration of total protein (TP) was measured through spectrophotometry and the protein fractions by means of eletrophoresis in poliacrylamide (SDS-PAGE). Twenty-nine to 31 proteins were detected by densitometric tracing, with molecular weights varying from 19,160 to 250,000 Dáltons (Da). Reduction of the transferrin concentration and increase of acid ?1-glycoprotein level were verified in sheep that ingested 75% and 100% of the plant, immediately before dying. Also, reduction of concentration of IgG heavy chain was evident in M3 and M4, in G3 animals, as well as the level IgG light chain in M2, M3 and M4 of this group, suggesting interference in the immune function in poisoned sheep, especially in those with higher level of the plant on the diet. It is inferred that these proteins can be utilized as auxiliary indicators to diagnose intoxication by I. asarifolia.KEYWORDS: Ipomoea asarifolia; poisonous plants; sheep.